Konsep Pendidikan Keluarga Islam - Fahri Hidayat (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2016)
Abstract: This paper focuses on the concept of family education from the Islamic perspective. This paper assumes that globalization has a negative effect one which of them is young Indonesian erosion of moralty. Therefore, it is necessary to revitalize the family’s education which is built on the foundation of monotheism, supported by pillars of teaching, and has the ultimate goal of forming perfect human being. Keyword: Family Education, Tauhid, Moralty.